Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian pada Dapur ‘02 Cimareme - Aldy Santo Hegiarto; Sri Ayuni (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the effect of price and product quality on purchasing decisions at Dapur ‘02 Cimareme. The research was driven by the growing importance of pricing strategies and product quality in influencing consumer behavior within the increasingly competitive culinary industry. A quantitative approach with a descriptive-verificative design was employed. Data were collected through questionnaires administered to 100 respondents and analyzed using multiple linear regression. The descriptive analysis results indicate that both the price and product quality variables were categorized as good. The results further show that price has a positive and significant effect on purchasing decisions, whereas product quality does not have a significant effect when examined individually. Nevertheless, both variables jointly exert a significant influence on purchasing decisions. In addition, the coefficient of determination reveals that price and product quality explain 58.3% of the variance in purchasing decisions, while the remaining 41.7% is attributable to other factors beyond the scope of this study.